Production of High Surface Area Activated Carbon from Grass (Imperata) - Abdulmajeed, Yossor R.; Mahmood, Noor AL-Huda Jabber (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
In this work the production of activated carbon (AC) from Imperata is done by microwave assisted Potassium hydroxide (KOH) activation and using this activated carbon for the purpose of the uptake of amoxicillin (AMX) by adsorption process from aqueous solution. The effects for irradiation power (450-800W), irradiation time (6-12min) as well as impregnation ratio (0.5-1 g/g) on the AMX uptake and yield AMX uptake at an initial concentration of AMX (150 mg/g). The optimum conditions were 700 W irradiation power, 10 min time of irradiation, as well as 0.8 g/g impregnation ratio with 14.821% yield and 12.456 mg/g AMX uptake. Total volume of hole and the area of the surface (BET) are 0.3027 m³/g, and 552.7638 m²/g respectively. The properties for the activated carbon were examined via Scanning Electron Microscopy (SEM).